Comparative Analysis of Leaf Anatomy of Forage Grasses Submitted to Freezing Temperature Stress - Filho, João Manetti [UNESP]; Gonçalves, Izabeli Bertini Lara; de Oliveira, Carolina Maria Gaspar; de Almeida Gonçalves, Ricardo [UNESP]; Hernandez, Fernando Braz Tangerino [UNESP]; Caramori, Paulo Henrique; Martins, Aline Redondo [UNESP] (Friends Science Publishers, 2023)
Frost causes frequent damage to pasture and limits continuous foraging under field conditions in many regions. Histological sections of plant tissues after a cold can provide important information to confirm the temperatures at which tissue death begins. This study was aimed to analyze anatomical alterations that may occur in forage leaves submitted to freezing temperatures in a controlled environment. The studied species were sorghum (Sorghum bicolor (L.) Moench.), Marandu (Brachiaria brizantha cv. Marandu), Millet (Pennisetum glaucum (L.) R. Br.). The plants were grown in a greenhouse for two months and then exposed in a growth chamber to temperatures of: 0.2 (control), -2.7 and -4.1°C. After the cold exposure, leaf tissue samples were sampled to measure the thickness of the cells in the adaxial and abaxial epidermis, bulliform cells, radiated parenchyma, and total leaf thickness. The results indicated a positive relation between freezing-temperature and a decreased thickness of the analyzed tissues. In crux, thickness of lower leaf epidermis under freezing temperatures was distinctly different among the investigated forage species, and was taken as a criterion to identify cold tolerance in these species.
Keywords: Cold damage; Correlation; Epidermis thickness; Forage grasses; Leaf tissues